Principles of inorganic materials design - Lalena, John N.; Cleary, David A.; Duparc, Olivier B. M. Hardouin (Wiley, 2020)
"With its proven concept, this textbook introduces topics relevant to the design of new materials. It covers a wide range of topics in the area of inorganic materials structure/property relations and materials behavior across length scales. New to this third edition are chapters specifically on computational materials science, compound semiconductors, intermetallic compounds, and covalent compounds. Also, there are expanded discussions on several topics, including microstructural considerations, transport properties, magnetic and dielectric properties, and nanomaterials. This textbook therefore provides a state-of-the-art introduction to inorganic materials design for advanced students of materials science, chemistry and engineering"--